Cadmium and lead levels of sweet potato (Ipomea batatas Lam.) leaves cultivated in the province of Tarlac - Belen, Neil Aldrin B.
Human exposure to cadmium (Cd) and lead (Pb) can be attributed to two routes: natural and anthropogenic activities. These heavy metals can be introduced in the human diets through the consumption of contaminated leafy vegetables and other agricultural crops. In this study, levels of Cd and Pb in locally cultivated sweet potato leaves samples (n=24) obtained from Sapang-Moncada, Tarlac, Philippines were determined using validated AOAC Official Method 999.11 (using flame atomic absorption spectrophotometry (F-AAS)) and the following parameters were established: (a) Limit of Detection (LOD) of 0.012 mg/kg for Cd, and 0.12 mg/kg for Pb; (b) Limit of Quantification (LOQ) of 0.04 mg/kg for Cd and 0.4 mg/kg for Pb; (c) Accuracy with correlation coefficient (r2) of 0.9976±0.00158 for Cd and 0.9975±0.002194 for Pb; and, (d) Percent (%) Recovery of 113% to 111%, for Cd and Pb, respectively. The Cd and Pb levels in sweet potato leaves samples ranged from 0.1449 to 0.5936 mg/kg, 0.3248 to 3.065 mg/kg, respectively. Generally, the Cd levels in sweet potato leaves samples were higher than the maximum level (ML) for leafy vegetables at 0.2 mg/kg for Cd and 0.3 mg/kg for Pb (CODEX STAN 193-1995). Dietary exposure assessment of Cd and Pb in the consumption of sweet potato by Filipino consuming population with respect to national data (7th Philippine National Nutrition Survey 2008), concluded that the estimates of dietary exposures for Cd were less than 100% of the Provisional Tolerable Monthly Intake (PTMI), 0.025 mg/kg bw/month established by the 73rd Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 2010 for Cd. Also, the dietary exposures for Pb concluded that the estimates of dietary exposures for Pb were less than 100% of the previous PTWI (Provisional Tolerable Weekly Intake) (previously withdrawn in 2010), 0.025 mg/kg bw/week set for Pb.